NEGATIVE MARKETING IN THE COSMETICS INDUSTRY: THE EFFECT OF GREENWASHING PERCEPTIONS ON PURCHASE INTENTION THROUGH BRAND IMAGE - Utami, Christina Whidya; Teofilus, Teofilus; Somawiharja, Yohannes; Tanan, Antonius; Salsabila, Aisyah; Emantyo, Yosef Evandro; Tsai, Chia Han (Jurnal Aplikasi Manajemen, 2022)
With the rise of the sustainable lifestyle movement, the Javanese people are becoming more aware of the need to buy environmentally friendly products, especially cosmetics. The facts in the field show that the company's marketing practices do not support the growing trend of buying eco-friendly cosmetics or the number of people who buy them. This study aimed to determine how consumers' views about greenwashing affect the purchase intention for environmentally friendly cosmetics in the Java Island region, with the brand image as a moderator. The methodology of this research is a combination of a descriptive method and a quantitative method. A descriptive technique and a quantitative approach are used to study the relationship and effect of one variable on another. The sampling technique in this study is non-probability sampling with a purposive sampling type. The sample in this study amounted to 110 respondents, and the data analysis used the SPSS program. The results showed that Greenwashing significantly affected the brand image but did not affect the purchase intention, and the brand image did not affect the purchase intention. Moreover, the total effect showed that greenwashing did not affect the purchase intention through the brand image. So this research concludes that a greenwashing phenomenon can easily produce brand image.